2019
DOI: 10.1177/2158244019855847
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Innovation and Performance in Private Companies: Systematic Literature Review

Abstract: This article conducts a systematic literature review (SLR) on the relationship between innovation and performance in private companies. The research corpus was based on research protocol systematization. Dissemination of knowledge was examined in two stages: the summary of general corpus characteristics, and the content analysis performed according to the categories that emerged via the study's themes. Relationships among authors, co-citations, keywords, and centrality statistics were identified through algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
(116 reference statements)
2
22
0
1
Order By: Relevance
“…Thus, the results from our overall sample provide support for the viability of those three innovation strategies. The findings are consistent with studies that extol the benefits of creative innovation (Bach et al, 2019;Damanpour and Evan, 1984;Damanpour et al, 2009), imitative innovation (Wang et al, 2019), and the synergistic (Lee et al, 2019) or combinative effects of different types of innovation (Arranz et al, 2019;Ballot et al, 2015;Doran, 2012;Tavassoli and Karlsson, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the results from our overall sample provide support for the viability of those three innovation strategies. The findings are consistent with studies that extol the benefits of creative innovation (Bach et al, 2019;Damanpour and Evan, 1984;Damanpour et al, 2009), imitative innovation (Wang et al, 2019), and the synergistic (Lee et al, 2019) or combinative effects of different types of innovation (Arranz et al, 2019;Ballot et al, 2015;Doran, 2012;Tavassoli and Karlsson, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Managerial innovation enhances firm performance because innovative activities make a firm more competitive and transforms a firm's internal capabilities (Alzuod & Kharabsheh, 2015;Rogers, 1998). Previous research found that managerial innovation in enterprises is closely related to the firm performance dimensions and the quality of services (profitability and market share as important non-financial firm performance indicators), and positively increases customer satisfaction and Return of Investment (ROI) (Daugherty, Chen, & Ferrin, 2011;Liao, Wang, Chuang, Shih, & Liu, 2010;Uzkurt, Kumar, Kimzan, & Eminoglu, 2013). The following hypothesis reflects the prediction that managerial innovation activities will affect management performance.…”
Section: Research Hypothesesmentioning
confidence: 86%
“…This research also verifies that training conducted in the hotels for the employees could enhance the hotel's organisational performance as stated by (Garavan et al, 2021;Kanapathipillai & Azam, 2020;Samwel, 2018;Gobal et al, 2018;Daniel, 2018;David et al, 2005;Jenks et al, 2007) in previous studies. Additionally, a hotel that innovates could also amplify its organisational performance as illuminated by (Koay & Muthuveloo, 2021;Asif et al, 2019;Tatiana et al, 2019;Tajeddini's, 2012) that innovation significantly influences and enhances organisational performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have discovered that innovation significantly leads to organisational performance and job satisfaction (Asif et al, 2019;Tatiana et al, 2019).…”
Section: Innovation and Relationship With Job Satisfaction And Organisational Performancementioning
confidence: 99%